INDUCTION OF GONADAL MATURATION OF POND CULTURED MALE TIGER SHRIMP, Penaeus monodon WITH DIFFERENT DOSAGES OF GONADOTROPIN RELEASING HORMONE ANALOGUE AGAINST EYE STALK ABLATION - Asda Laining; Usman Usman; Rachman Syah (Indonesian Aquaculture Journal, 2016)
Very low naturally mating rate of pond-reared tiger shrimp broodstock is probably due to the slow maturation of the male stock. The aim of this study was to evaluate the salmon gonadotrophin releasing hormone analoque (sGnRHa) in stimulating the gonadal maturation of male stock of pond-reared tiger shrimp. The treatments were three dosages of sGnRHa at 0.1 (OV-1), 0.2 (OV-2), and 0.3 (OV-3) mL/kg of shrimp weight and control was eye stalk ablation (AB). The sGnRHa was administered via injection three times with one week interval. Male stocks with average initial body weight of 82.1 g were randomly distributed into four of 10 m3 concrete tanks, 26 males for each tank. Variables observed were performances of spermatophores and profiles of amino acid and fatty acid of muscle of the male stocks. After induction, number of male maturing indicated by spermatophores releasing from terminal ampullas was higher in shrimp induced with OV-1 (80.8%) compared to control which was only 46.1%. Furthermore, shrimp treated OV-2 had the highest spermatophore weight of 0.16 g compared to control (0.11 g) and other two groups. Amino acid profiles improved as the dose of sGnRHa increased up to 0.2 mL/kg from 61.23% for ablated male becoming 71.27% for OV-2. Total fatty acid also tended to improve by increasing the dose of hormone injection, however, the ablated male had higher total fatty acid content than that of OV-1. The present finding demonstrated that the dose of sGnRHa to stimulate the gonadal maturation of pond-reared male tiger shrimp could be applied at range between 0.1-0.2 mL/kg of shrimp weight.